Implementasi Pelayanan Publik Terhadap Penanganan Pengaduan Masyarakat Tentang Data Ganda pada Instansi Dinas Kependudukan dan Catatan Sipil Kabupaten Gresik - Moh. Masyhur Arif* (Airlangga Development Journal, 2018)
If  connected  with  the  public  administration,  service  is  the  quality  of bureaucrat service to the community. The word quality has many different and varied definitions ranging from the conventional to the more strategic ones. The conventional definition  of quality usually illustrates the direct characteristics of a product, of which there are five indicators of public service, namely Reliability marked the proper service and correct; The tangibles are characterized by the adequate provision of human resources and other resources; Responsiveness, characterized by the desire to serve consumers quickly;  Assurance, marked the level of attention to ethics and moral  in  providing  services,  and  empathy,  which  mark  the  level  of willingness to know the wishes and needs of consumers.